The Association between Earnings Quality and Regulatory Report Opinions in the Accounting Industry - Zhang, Tracey Chunqi (Institutional Knowledge at Singapore Management University, 2006)
We compare the outcome of two different information systems – self regulation versus private sector regulation – in the accounting industry. Under the Sarbanes-Oxley Act, Public Company Accounting Oversight Board (PCAOB) inspections replaced American Institute of Certified Public Accountants (AICPA) peer reviews of auditors. Peer review opinions are useful with respect to decisions about hiring and firing of auditors (Hilary and Lennox, 2005); therefore, the question remains what are the benefits of incurring the cost to replace a selfregulatory system with a private regulatory agency. We examine the usefulness of these two information systems at distinguishing earnings quality at firms audited by the reviewed auditors. We find opinions from the PCAOB inspection are able to distinguish earnings quality (accounting discretion and earnings informativeness) whereas the peer review opinion does not. Given that the PCAOB inspection report opinions are associated with earnings quality, we next identify characteristics associated with auditors that receive a positive PCAOB opinion. We find they are larger (measured by the number of professional staff) and are more independent of clients.